Yttrium iron garnet – lead-barium titanate particulate multiferroic composites. (27th July 2018) - Lisnevskaya, Inna V.; Myagkaya, Ksenia V.; Bobrova, Irina A.
ABSTRACT: Ba1− x Pb x TiO3 /Y3 Fe5 O12 particulatecomposites with х = 0–1 were synthesized. The composites (100-y) wt.% Ba0.9 Pb0.1 TiO3 – y wt.% Y3 Fe5 O12 with у = 40–50 wt.% exhibit ME coupling coefficient ΔЕ/ΔH of ∼10 mV/(cm·Oe) due to the prominent piezoelectric properties. ME response in Ва1−х Pbx TiO3 /Y3 Fe5 O12 ceramics with х = 0.35−1 is precluded by a high content of pyrochlore-type Y2 Ti2 O7 that forms through chemical interfacial interaction. An increase in sintering temperature to 1300°С was found to be inappropriate to obtain phase-pure ВаTiO3 /Y3 Fe5 O12 ceramics due to the partial decomposition of Y3 Fe5 O12 to yttrium orthoferrite YFeO3 .